STUDY OF HAMID OLIMJON’S SCIENTIFIC HERITAGE BASED ON GENRE CLASSIFICATION AND MANUSCRIPT SOURCES - Mukhammadova Munisa Mukhibullaevna (International Journal of Literature and Language Studies, 2026)
This article analyzes the genre classification of Hamid Olimjon’s scholarly heritage based on manuscript collections and archival materials. The writer’s academic works in literary studies, folklore studies, and literary criticism are examined as distinct categories, revealing their content and scientific significance. Special attention is given to his views on the periodization of Uzbek literature, his research on Alisher Navoi, studies devoted to representatives of classical and Jadid literature, and his works on folklore and epic heritage. The study systematizes these materials and highlights Hamid Olimjon’s theoretical thinking, methodological approach, and contribution to literary scholarship. The article also emphasizes the relevance of classifying manuscript sources in modern textological research.